2013
DOI: 10.1097/jcp.0b013e318283983f
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Morbidity With Risperidone or Paliperidone Treatment

Abstract: A post hoc analysis of the risperidone (RIS)/paliperidone (Pali) clinical trials database comprising 64 studies was conducted. Risk of sudden death, cardiovascular (CV), and cerebrovascular events during RIS or Pali treatment was estimated. Treatment emergent CV adverse events were identified using 7 prespecified Standardised MedDRA Queries as follows: embolic/thrombotic events, cerebrovascular disorders, ischemic heart disease, cardiac arrhythmias, cardiac failure, torsades/QT prolongation, and convulsions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…[91][92][93][94] A meta-analysis suggested a significantly elevated incidence of cardiac events compared with placebo. 95 A marked prolongation of cardiac repolar ization at supratherapeutic doses was observed in a dog model. 96 Nonetheless, cases of sudden cardiac death caused by risperidone treatment have not been reported.…”
Section: Antipsychotic and Antidepressant Drugsmentioning
confidence: 97%
“…[91][92][93][94] A meta-analysis suggested a significantly elevated incidence of cardiac events compared with placebo. 95 A marked prolongation of cardiac repolar ization at supratherapeutic doses was observed in a dog model. 96 Nonetheless, cases of sudden cardiac death caused by risperidone treatment have not been reported.…”
Section: Antipsychotic and Antidepressant Drugsmentioning
confidence: 97%
“…A longitudinal epidemiological study of nearly 4000 men in Canada studied QTd and reported that heart rate and QTd predicted sudden cardiac death, but QT did not (Cuddy et al 2009). This finding suggests that QTc prolongation probably should not be regarded as the sole predictor of cardiac events in psychopharmacological treatments (Shah and Hondeghem 2005;Hondeghem 2006;Gopal et al 2013;Townsend and Brown 2013). To date, there are few studies that have examined the drug effects on QTd in children.…”
Section: Discussionmentioning
confidence: 99%
“…Given the incomplete consensus on which cardiac conduction variables are reliable endpoints for predicting drug-induced torsades, there is increased interest in other variables such as QT dispersion (QTd) (Shah and Hondeghem 2005;Hondeghem 2006;Gopal et al 2013). QTd is a general measure of ventricular recovery times and is calculated by subtracting the minimum QT interval from the maximum QT interval across ECG leads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of these receptors leads to tachycardia. 38 A systematic literature review (comprising 102 reports and 185 patients with case-level data) described the cardiovascular effects consequent to overdose of five common atypical antipsychotic medications and found that among patients with single-substance ingestion, tachycardia occurred in the majority of quetiapine and olanzapine ingestions ( . Warner et al 35 reported that 111 patients on various typical antipsychotic drugs had a significantly higher heart rate (HR) compared to 42 unmedicated controls (83 6 14 vs. 72 6 14 beats/min), although largely within the normal range.…”
Section: Chronotropic Effectsmentioning
confidence: 99%